The Influence of time perspective and personality traits on the psychological well-being of Ukrainian refugees in Europe - KELLER, Vladyslava (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2023)
Background. The Russian invasion of Ukraine in 2022 led to a sharp increase in the number of Ukrainian refugees in Europe. Due to the war and the subsequent need to adapt to new socio-cultural conditions, the mental health of this population is particularly vulnerable. People who have been forced to leave their country experience significant stress and are prone to developing symptoms of anxiety and depression. While psychopathology in this context has been well researched, protective factors that could potentially contribute to a better adjustment of Ukrainian refugees in the new environment have been less frequently studied. Accordingly, this study aims to fill this gap by examining the role of time perspective and personality traits in influencing the psychological well-being of Ukrainian refugees. Methods. A sample of 599 Ukrainian refugees from different European countries was studied using three key instruments: the Zimbardo Time Perspective Inventory, short version (ZTPI-15), the Big Five Personality Inventory, short version (BFI-10), and the Singer-Wheeler Life Satisfaction Scale (SWLS). Correlation and hierarchical regression analyses were used to determine the relationships between these constructs. Results. Both time perspective and personality traits were shown to predict subjective well-being significantly. In particular, refugees who demonstrate greater openness, emotional stability, and friendliness report higher levels of life satisfaction. Similarly, positive orientations toward the past and future were associated with increased well-being, while negative orientations were associated with decreased well-being. In contrast, conscientiousness, extraversion, and fatalistic orientation to the present were not significant predictors of subjective well-being, which is at odds with some existing literature. Conclusions. These findings emphasize the importance of considering both time perspective and personality traits in understanding the psychological well-being of Ukrainian refugees. They also point to the potential benefits of interventions to develop adaptive time perspectives and positive personality traits. Further research is needed to develop and evaluate such interventions.